DESCRIPTION OF THE KNOWLEDGE LEVEL OF ADOLESCENT WOMEN ABOUT ANEMIA - Made Suandika; Etika Dewi Cahyaningrum; Woung Ru-Tang; Refa Teja Muti; Yuris Triliani; Dwi Astuti (Sekolah Tinggi Pariwisata Mataram, 2023)
A lack of sufficient or adequate red blood cells results in anemia, which lowers the blood's ability to transport oxygen. Despite having a normal blood pressure, symptoms and indicators of fainting include weakness, pallor, and dizziness. Special consideration must be given to the significant occurrence of anemia in adolescent girls. The majority of anemia prevention and control initiatives to date have focused on populations of pregnant women, while little emphasis has been paid to early prevention of anemia in adolescent women who are future mothers. The goal of this study was to determine whether adolescent womens had good, sufficient, or poor understanding about anemia.A descriptive survey was employed for the research, which was conducted with a sample size of 100 respondents. Total sampling was used to draw samples from the entire community. A questionnaire was employed as the study tool, and SPSS for Windows was used to process the data. Approach for unvaried data analysis with frequency distribution. There are 100 second grade students about anemia, who have good knowledge of 72 students (72%), only 23 students (23%), and less than 5 students (5%). According to the study's findings, the student adolescent womens have a generally high level of knowledge.